2022
DOI: 10.1038/s41598-022-23517-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marigold (Tagetes erecta L.) on soil microbial communities in continuously cropped tobacco fields

Abstract: Root-knot nematode disease is a catastrophic soil-borne disease in tobacco production. The regulation of natural microbial communities is considered a good disease management approach to suppress the incidence of soilborne diseases. In this study, the effects of tobacco (Nicotiana tabacum L.)-marigold (Tagetes erecta L.) rotation on the diversity and structure of soil microbial communities in continuously cropped tobacco fields were analyzed to manage this devastating pathogen. The results showed that the soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Different plants shape speci c core rhizosphere microbial communities even when they grow in the same soil. However, long-term net cultivation of a single plant variety often leads to the accumulation of plant pathogens in the soil, which destroys and reduces the complexity of underground microbial communities, leading to reduced crop yield (Huang et al 2022; Mariotte et al 2018). Tobacco bacterial wilt is a devastating soil-borne disease caused by Ralstonia solanacearum, and diseased soil and residues are the main causes of tobacco bacterial wilt (Ameen), which can easily occur under long-term continuous cropping (Kawasaki et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different plants shape speci c core rhizosphere microbial communities even when they grow in the same soil. However, long-term net cultivation of a single plant variety often leads to the accumulation of plant pathogens in the soil, which destroys and reduces the complexity of underground microbial communities, leading to reduced crop yield (Huang et al 2022; Mariotte et al 2018). Tobacco bacterial wilt is a devastating soil-borne disease caused by Ralstonia solanacearum, and diseased soil and residues are the main causes of tobacco bacterial wilt (Ameen), which can easily occur under long-term continuous cropping (Kawasaki et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, crop rotation is used to maintain the rich array of plant species in the ecosystem (Larkin 2015), thereby reducing pathogen stress on plants via improving the diversity and structure of rhizosphere microorganisms (Cook 2006;D'Acunto et al 2018). Studies have proven that a reasonable crop rotation pattern can coordinate soil nutrients (Jagadamma et al 2008), optimize soil chemical properties, enhance the circulation and cooperation of soil microorganisms (Ben Abdallah et al 2023), and reduce the occurrence of soil-borne diseases (Huang et al 2022;Ma et al 2023;Niu et al 2017a; Yang et al 2018). For example, three-year radish green manure rotation had a cumulative effect on the soil inhibition of tomato-related pathogens, and tilting radish signi cantly reduced the occurrence of tomato bacterial wilt (Ben Abdallah et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Soil pH, organic matter, total potassium, available boron, zinc, CEC, and exchangeable magnesium under crop rotation were increased compared to soil under continuous cropping ( Verma et al, 2021a , 2022a , b ; Chen and Zeng, 2022 ). Previous studies on crop rotation and intercropping of tobacco and rice, corn, garlic, green manure, etc., found that crop rotation can effectively reduce the impact of tobacco continuous cropping ( Huang et al, 2019 , 2022 ; Wang et al, 2022 , 2023 ). Especially for soil microorganisms, crop rotation can effectively improve the population properties of soil microorganisms, as imbalances of soil microbial community are a common phenomenon caused by continuous cropping.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, different planting methods have a great influence on RKN. Long-term continuous cropping of peanuts will undoubtedly aggravate the occurrence of RKN disease [10], and the traditional approach tends to use crop rotation to control RKN [11]. Bacterial community and structural changes are closely related to RKN disease.…”
Section: Introductionmentioning
confidence: 99%